PERLINDUNGAN HUKUM TERHADAP DATA PRIBADI KONSUMEN PENGGUNA JASA OJEK ONLINE - Wa Ode Zamrud; Muhammad Syarifuddin (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2022)
The purpose of writing is to know legal protection to consumer in using transportation service online and responsibilities of business players when the loss from the customers in using transportation service online. From analysis discussed can be concluded that legal protection given to the entrepreneurs transportation service based application where in terms of transportation has been set up in article 10 act - act number 22/2009 about traffic and publik transportation, government regulation no 41 years 1993 on public transportation and transportation minister decree number 35 years 2003 regarding minivans people in the street and public transports and if consumers feel the quantity and quality of services that does not conform so consumer entitled 2 get compensation loss worth in accordance with the provisions article 19 clause (1 and paragraph (2) act - act number 8 1999 on consumer protection. The development of business in city Baubau good, in terms of industry manufacturing, and facilities must be provided to support business development itself, hance by high demand for motorcycle taxi online necessary the study of Indonesia kururio ojek so users of online shelter law.